Gaya Hidup dan Pengaruhnya terhadap Minat Beli Konsumen dalam Perspektif Kualitas Produk - Nur Hayati; Deni Jayadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Abstract: This research aims to analyze the influence of product quality and lifestyle on the purchase intention of Mayoutfit consumers. The research method employed is quantitative and verificative, utilizing primary data collected through questionnaires and secondary data from literature reviews. The results of the study indicate that, simultaneously, product quality and lifestyle significantly influence consumer purchase intention. Furthermore, on a partial basis, both product quality and lifestyle exhibit positive and significant effects on the purchase intention of Mayoutfit consumers.